Relationship Between Ulama And Umara In Socialize The Vaccination Program During Covid 19: A Study Of Indonesian Fiqh - Fauziyah, Ulil (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
Abstract: The Covid 19 pandemic has had a crisis impact, especially in the health, economic and social fields. To restore it requires cooperation from various parties, including cooperation between ulama and umara. This research aims to find out how the relationship exists between ulama and umara in socializing the Covid-19 vaccination program from the perspective of Indonesian jurisprudence. This research uses a literature review (library research) with a qualitative approach that describes how the idealism of the relationship between ulama and umara in the archipelago in socializing the vaccination program during Covid 19: a study of Indonesian Fiqh. Ulama and umara in Indonesia are elites who have different roles in society. Ulama and Umara in Indonesia reflect associative social patterns. Where ulama and umara tend to work together and unite at both the central and regional levels in implementing various policies during the Covid 19 era. The success of socializing the Covid 19 vaccination in Indonesia is the success of various parties, dominated by the elite, namely ulama and umara. Ulama play a role in explaining the legal aspects of the permissibility and importance of the Covid 19 vaccine. As a form of body immunity through door to door, religious gatherings, places of worship and on various occasions. Meanwhile, Umara provides and carries out the Covid-19 vaccine program for the community through hospitals, health centers, clinics, offices or places that have been designated as places for the Covid-19 vaccine.